First-episode mania after COVID-19: A case series in Iran - Saeidi, Mahdieh; Rezvankhah, Tara; Pereira-Sanchez, Victor; Rafieian, Maryam; Shariati, Behnam; Esmaeeli, Soode Tajik; Emamikhah, Maziar; Alavi, Kaveh; Shabani, Amir; Soraya, Shiva; Kashaninasab, Fatemeh; Mirfazeli, Fatemeh Sadat (Frontiers in Psychiatry, 2023)
Abstract Background: Increasing reports of manic episodes in patients during acute infection with COVID-19 have been documented since the pandemic began, including among individuals without previous personal or family history of bipolar disorder. As infections and autoimmunity have putative roles in bipolar disorder, we aimed to document the clinical presentations, associated stressors, family aggregation patterns, and brain imaging and electroencephalographic correlates in a series of patients with episodes of mania that emerged shortly after COVID -19 infections. Methods: We obtained all relevant clinical information from twelve patients whose first manic episode started within a month of COVID-19 infection and were treated at Rasool-e-Akram hospital and Iran psychiatric hospital, two tertiary medical centers in Tehran, Iran, in 2021. Results: Patients had a mean age of 44. The interval between the onset of symptoms of COVID and mania ranged between 0-28 days (mean: 16.25, median: 14 days); it was observedly to be shorter in patients with a family history of mood disorders but not in those receiving corticosteroids. Alongside a descriptive overview of our sample, we provide detailed narrative descriptions of two of the cases for illustrative purposes and discuss our observations in the context of other cases reported elsewhere and the state of the art regarding infectious diseases, COVID-19, and bipolar disorder as reported in previous literature. Conclusions: Our case series documents observational and naturalistic evidence from a dozen of cases of mania in the context of acute COVID-19, which, while limited, calls for analytical research of the phenomenon, and points at a family history of bipolar disorder and the use of corticosteroids as factors for particular focus.